Kearifan Lokal Tarian Tortor : Sebuah Kajian Teologi Harapan dalam Tarian Tortor pada Pesta Pernikahan Batak Toba - Susilawati Panjaitan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Thei Tor-tori dancei isi onei ofi thei culturali legaciesi ofi thei Bataki Tobai peoplei thati carriesi deepi meaning,i especiallyi ini traditionali ceremoniesi likei weddings.i Thisi dancei isi noti justi entertainmenti buti alsoi ai meansi toi conveyi prayersi andi hopes,i bothi fori thei bridei andi groomi asi welli asi fori thei familiesi andi communitiesi present.i Everyi movementi ini thei Tor-tori dancei containsi symbolism,i suchi asi respecti fori elders,i hopesi fori happiness,i unity,i andi blessings.i Throughi thisi dance,i thei Bataki Tobai peoplei alsoi maintaini ai spirituali connectioni withi theiri ancestorsi andi strengtheni theiri culturali identityi ini thei facei ofi globalization.i Thisi studyi examinesi thei Tor-tori dancei throughi thei lensi ofi thei theologyi ofi hope,i whichi revealsi thei profoundi meaningi ofi hope,i protection,i andi blessingsi conveyedi throughi eachi movement.i Thei dancei alsoi reflectsi spirituali communicationi thati connectsi humansi withi Godi andi thei universe.i Asi parti ofi ai traditioni stilli relevanti ini thei moderni era,i Tor-tori noti onlyi preservesi culturali valuesi buti alsoi becomesi ai symboli ofi pridei fori thei Bataki Tobai community.i Byi maintainingi thisi tradition,i theyi introducei Indonesia'si richi culturei toi thei worldi whilei alsoi strengtheningi sociali tiesi withini theiri community.